PENERAPAN LATIHAN SKIPPING TERHADAP DAYA LEDAK OTOT TUNGKAI PADA PEMAIN CLUB BOLA VOLI B. SRIKATON MUSI RAWAS - Agus Tri Untoro; Muhammad Supriyadi; Wawan Syafutra (LPPM STKIP Bina Bangsa Meulaboh, 2024)
This research aims to determine whether there is a significant increase in the explosive power of leg muscles in B. Srikaton Musi Rawas Volleyball Club players after being given skipping training. The research method used was an experimental method, namely statistics to determine the effect of skipping training. The population and sample for this research were the B. Srikaton Musi Rawas Volleyball Club players, totaling 24 players. The research sample consisted of 12 players taken using the random sampling method. The data collection technique uses a vertical jump test instrument. The data analysis technique uses the t-test statistical formula. The research results obtained that the titing was greater than ttable or 4.062> 2.201, thus Ha was accepted and Ho was rejected. Conclusion: There was a significant increase in the explosive power of the leg muscles in the B. Srikaton Musi Rawas Volleyball Club players after being given skipping training.